2020
DOI: 10.1103/physrevfluids.5.011301
|View full text |Cite
|
Sign up to set email alerts
|

Drop dynamics of viscoelastic filaments

Abstract: The stretching of viscoelastic polymer solutions close to break-up can create attached drops on a filament, whose properties and dynamics are little understood. The stretching of capillary bridges and the consecutive filament, until its breakup, can be quantified using diameter-spacetime diagrams, which demonstrate hierarchy, as well as, asymmetry of satellite drops around a big central drop. All drops experience migration, oscillation and merging. In addition, the position of the minimum diameter on the filam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…By the same idea, we have estimated the relaxation time of the PEO solution as the inverse of the shear rate where η = 0.95η 0 , i.e., λ = λ C (0.95 −1/k − 1) −1/2 . Recently, Pingulkar et al [41] have measured the relaxation time of the PEO solutions for c = {200, 450, 600, 1000, 2000} ppm using capillary breakup extensional rheometer (CaBER). They have found that the relaxation time increases with increase in c of PEO following a power law : λ CaBER = 1.2c 0.83 .…”
Section: Relaxation Time Of Peomentioning
confidence: 99%
“…By the same idea, we have estimated the relaxation time of the PEO solution as the inverse of the shear rate where η = 0.95η 0 , i.e., λ = λ C (0.95 −1/k − 1) −1/2 . Recently, Pingulkar et al [41] have measured the relaxation time of the PEO solutions for c = {200, 450, 600, 1000, 2000} ppm using capillary breakup extensional rheometer (CaBER). They have found that the relaxation time increases with increase in c of PEO following a power law : λ CaBER = 1.2c 0.83 .…”
Section: Relaxation Time Of Peomentioning
confidence: 99%
“…Further analysis of the diameter can be used to obtain the extensional viscosity as a function of time and Hencky strain. These results are given in Pingulkar et al 14 Based on the solution properties, several dimensionless numbers can be defined. The Deborah number, De = λ/τ R , represents a ratio of the viscoelastic time, λ, to the Rayleigh inertiocapillary time: τ R = ρR 0 3 /σ.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…For Newtonian fluids, during this liquid transfer, solution pools are formed on the end plates of a stretched liquid bridge. On the other hand, a stretched viscoelastic liquid bridge forms a persistent thin filament [9][10][11][12][13][14] along with the solution pools.…”
Section: Introductionmentioning
confidence: 99%

Liquid Transfer for Viscoelastic Solutions

Pingulkar,
Peixinho,
Crumeyrolle
2021
Preprint
Self Cite
“…2010; Malkin, Arinstein & Kulichikhin 2014; Turkoz et al. 2018 b ; Pingulkar, Peixinho & Crumeyrolle 2020). Generally, more secondary droplets tend to be formed at smaller viscosities or smaller elasticities (Bhat et al.…”
Section: Introductionmentioning
confidence: 99%